The Fairy Tale as a Place of Memory in the Context of Intergenerational Communication - Chudnovskaya, Irina N.; Lipatova, Maria E. (Journal of History Culture and Art Research, 2020)
A fairy tale as a form of a cultural code is the most important tool for cultural and ethnic socialization, the transfer of social experience, values, and worldview. Modern society is characterized by a high level of technologization, standardization, and universalization of the communication process which leads to the formation of new social practices of communication of various social groups. The article is focused on highlighting the functional and activity role of a fairy tale in the formation of the social memory of the younger generation and the features of the implementation of intergenerational communication through the fairy tale. In the article, a fairy tale as a place of memory in intergenerational communication is also analyzed using the methodological tools of the sociology of communication. The article discusses the detailing of the concept of “social memory”, types of social memory. With an emphasis on the identification function, the authors consider the main social functions of a fairy tale (cultural and ethnic, socializing, creative, holographic, developmental and therapeutic, lexical-shaped, recreational). The authors consider the activity aspect of the fairy tale as a place of memory is revealed, the interactional relations of communicants, conditioned by social changes and information and communication technologies, in their historical dynamics. The article analyzes the stage of transition from mythological knowledge to the need to carry out initiation practices with the transfer of secrets to the younger generation in encoded form, in the form of a fairy tale. The most significant stage can be called the transformation of a fairy tale into a verbal-poetic story of a fantastic, adventurous, novelistic, and everyday nature. The article analyzes the impact of information technologies on the form of fairy tale transmission as the destruction of the traditional narrative format from the older generation “by the word of mouth” and the exit of the fairy tale beyond the literary genre. In modern society, the range of communication agents in the transmission of social experience between generations has significantly expanded. There appear agents of non-family communication, which take part in the transmission of cultural memory and the formation of memory places in the younger generation. The authors note that in the communicative aspect, a fairy tale is a convenient form for transmitting cultural code, which can be adapted to current formats (Internet, animation, cinema, computer games, etc.). It is shown that the most important feature of the use of modern storytelling tools is the reduction of traditional emotionality in the interactive relationships of communicants, which leads to the erosion of traditional values and a decrease in the depth of intergenerational ties. This trend may lead to the risk of alienation of traditional values.